A Study of TI Group (IV) Synthesis Complexes Post-Metallocene for Olefin Polymerization: Synthesis and Characterization of Catalysts and Ligands for Olefin Polymerization (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Five modern catalysts have been synthesized with various ligand structures for polymerization of aqueous polar and non-polar olefins. New complexes of titanium [TiLCl2] Catalyst [TiLCl2] LH2=2-(3,5-Di-tert-butyl-2-hydroxybenzylamino-hydroxybenzylamino)-succinic acid] [Catalyst 1]} [Catalyst 2] with N and O as a pendant donor was synthesized. {LH2=2-(((2, 4-di-tert-butyl-6-hydroxybenzyl) amino] amino) acetic acid). Oxalic [Catalyst 3] Ti (IV) complexes have been synthesized, with Oxalic (TiL2Cl 2), Oxalic, Malonic and Succinic acid (LH= Oxalic), Malonic and Succinic acid) and Succinic [Catalyst 5] acids. Many of the above synthesized catalysts were tested for polar and non-polar olefins (MMA, MA, styrene) homo- polymerization as well as at ambient temperature for their catalytic activities in aqueous emulsion polymerization. The present work describes in greater depth the synthesis and characterization of both ligands and catalysts. For studies the elementary analyzer characterizations methods 1 H NMR, 13C NMR, HRMS, IR, UV-spectroscopy and CHN have been used.